Artificial Hydrogenases Based on Cobaloximes and Heme Oxygenase. Issue 10 (6th October 2016) - Bacchi, Marine; Veinberg, Elias; Field, Martin J.; Niklas, Jens; Matsui, Toshitaka; Tiede, D. M.; Poluektov, Oleg G.; Ikeda‐Saito, Masao; Fontecave, Marc; Artero, Vincent
Abstract: The insertion of cobaloxime catalysts in the heme‐binding pocket of heme oxygenase (HO) yields artificial hydrogenases active for H2 evolution in neutral aqueous solutions. These novel biohybrids have been purified and characterized by using UV/visible and EPR spectroscopy. These analyses revealed the presence of two distinct binding conformations, thereby providing the cobaloxime with hydrophobic and hydrophilic environments, respectively. Quantum chemical/molecular mechanical docking calculations found open and closed conformations of the binding pocket owing to mobile amino acid residues. HO‐based biohybrids incorporating a {Co(dmgH)2 } (dmgH2 =dimethylglyoxime) catalytic center displayed up to threefold increased turnover numbers with respect to the cobaloxime alone or to analogous sperm whale myoglobin adducts. This study thus provides a strong basis for further improvement of such biohybrids, using well‐designed modifications of the second and outer coordination spheres, through site‐directed mutagenesis of the host protein. Abstract : In the pocket : Novel cobaloxime‐based biohybrids display hydrogenase activity in aqueous media. This study paves the way for inexpensive and effective catalysts for hydrogen production that are capable of functioning in water (see figure). Changes in the coordination environment were investigated by taking advantage of the structural variety of binding pockets of hemoproteins.